`If you haven't got the contacts … you have no choice`: A figurational examination of unpaid work in football scouting in men's professional football in England - Griffiths, J.; Bloyce, D. (International Review for the Sociology of Sport, 2023)
Association football has been viewed as an industry with considerable lucrative career prospects; however, this has not prevented the use of unpaid staff throughout football in the UK. There has been increasing academic research regarding the professionalisation and commercialisation of football, yet there has been little acknowledgement of the role of those working in football in an unpaid capacity. Therefore, this paper examines the culture of unpaid work in football scouting, by exploring the motivations of 12 unpaid scouts at professional clubs, from a figurational perspective. Our findings suggest that scouts want to work in the industry because of their `love of the game`, in a `quest for excitement` in their career. Unpaid work was in the pursuit of experience and contacts, the latter of which was highly valued in the industry. Football clubs are enclosed figurations and the scouts placed importance on developing interdependent social relations to gain entry to the industry, demonstrating how football may be perceived nepotistic. The likelihood of gaining a paid role directly from an unpaid position was low and therefore the decisions to continually accept unpaid work represented the notion of fantasy-laden thinking.